2017
DOI: 10.4103/ijccm.ijccm_318_16
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in B.type Natriuretic Peptide and Related Hemodynamic Parameters Following a Fluid Challenge in Critically Ill Patients with Severe Sepsis or Septic Shock

Abstract: Context:Severe sepsis or septic shock.Aims:The aim of this study is to examine the effect of a fluid challenge on the B-type natriuretic peptide (BNP) and the hemodynamic state.Settings and Design:This observational study was conducted in an intensivist-led academic, mixed medical-surgical Intensive Care Unit.Subjects and Methods:Focused transthoracic echocardiogram, plasma BNP, and hemodynamic measurements were recorded at baseline and following a 500 ml fluid challenge in thirty patients. Independent predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Вместе с тем есть основания считать, что НУП могут быть взаимосвязаны с параметрами кровообращения в общей популяции больных, в том числе без снижения фракции изгнания ЛЖ, характерного для септической кардио патии. В различные сроки после поступления больных в ОРИТ выявлены корреляции между BNP или NTproBNP и конечно-диастолическим объемом ЛЖ [11,35], заклинивающим давлением в легочной артерии (ДЛА) [14], АДср, сердечным индексом [23], а также эхокардиографическими признаками диастолической дисфункции (характеристики трансмитрального потока) [36]. Последнюю считают наиболее ранним проявлением септической кардиопатии, когда еще нет снижения фракции изгнания ЛЖ [37].…”
Section: Discussionunclassified
“…Вместе с тем есть основания считать, что НУП могут быть взаимосвязаны с параметрами кровообращения в общей популяции больных, в том числе без снижения фракции изгнания ЛЖ, характерного для септической кардио патии. В различные сроки после поступления больных в ОРИТ выявлены корреляции между BNP или NTproBNP и конечно-диастолическим объемом ЛЖ [11,35], заклинивающим давлением в легочной артерии (ДЛА) [14], АДср, сердечным индексом [23], а также эхокардиографическими признаками диастолической дисфункции (характеристики трансмитрального потока) [36]. Последнюю считают наиболее ранним проявлением септической кардиопатии, когда еще нет снижения фракции изгнания ЛЖ [37].…”
Section: Discussionunclassified
“…Repeated fluid challenge administration until the heart is operating on the flat portion of the Frank-Starling curve may potentially lead to tissue/lung edema. Increases in cardiac filling pressures induced by fluid administration stimulates the release of atrial natriuretic peptide by myocardial cells ( 131 ), which is a physiological mechanism whereby the organism promotes elimination of excess fluid. However, it has been demonstrated that increased plasma atrial natriuretic peptide also promotes shedding of the endothelial glycocalyx, which may lead to tissue edema ( 132 ).…”
Section: Controversies Of Gdft and The Risk Of Fluid Overloadmentioning
confidence: 99%
“…Brain natriuretic peptides have been found to be associated with cardiac dysfunction in patients with septic shock. 17,18,28,29,32,36,37,39,41,46,[48][49][50][51] Elevated levels of BNP and NT-proBNP have been associated with reduced ejection fraction 17 and stroke volume, 39 global tissue hypoxia, 18 reduced cardiac index, 48 sepsis induced myocardial dysfunction, 50 prior cardiac dysfunction, 37,49,52 diastolic left ventricular size 51 and systolic as well as diastolic dysfunction. 29,32,36 On the contrary, BNP has been found to be a poor predictor of volume status in critically ill patients, including patients with septic shock.…”
Section: Brain Natriuretic Peptides Levels In Respect To Cardiac Fumentioning
confidence: 99%